Shamelessness and despair in America - Beauclair, Alain (My University, 2021)
This article offers a diagnosis of the current state of political rhetoric in America, arguing that the prevalence of shamelessness and despair in our age is a result of an injury to the imagination. Taking its bearings from both Aristotle and Dewey, it claims that this injury has its origins in our increasing inability to articulate the objects of our fear in a manner that fosters intelligent inquiry, and consequently inhibits our collective capacity to reconstruct our desires in a manner commensurate with our current circumstances. In an effort to meliorate this challenge, the article points in the direction of the potential fecundity in such positive dispositions as respect and goodwill.
Keywords: shamelessness; despair; Aristotle; imagination; fear